Stranded steel wire ropes Part 2. Specification for ropes for general purposes (BSI, 1987)
Ropes, Wire ropes, Steel-wire ropes, Strands, Design, Cores (ropes), Rope pitch, Breaking load, Diameter, Weight (mass), Tensile strength, Grades (quality)